Global population pharmacokinetics of the investigational Aurora A kinase inhibitor alisertib in cancer patients: rationale for lower dosage in Asia. (24th November 2017) - Zhou, Xiaofei; Mould, Diane R.; Takubo, Takatoshi; Sheldon‐Waniga, Emily; Huebner, Dirk; Milton, Ashley; Venkatakrishnan, Karthik
Abstract : Aims: This population pharmacokinetic analysis was conducted to describe quantitatively the regional differences and sources of interpatient variability on the apparent oral clearance of alisertib. Methods: A population pharmacokinetic analysis was performed on data from 671 cancer patients in Western countries and in Japan/East Asia to whom alisertib 5–150 mg once or twice daily (b.i.d.) was administered in multiple dosing schedules. The final model was used to simulate alisertib pharmacokinetics in patients in the West and East Asian regions in the single‐agent schedule of 7 days of dosing in a 21‐day cycle. Exposure–safety relationships for mechanism‐related antiproliferative toxicities (neutropenia, mucositis and diarrhoea) were estimated by logistic regression. Results: Alisertib pharmacokinetics were described by a two‐compartment model with four‐transit compartment absorption and linear elimination. The final model included a covariate effect of region on relative bioavailability, with patients in the East Asian region estimated to have a 52% higher bioavailability compared with Western patients. Population simulated exposure at 30 mg b.i.d. in patients in Asia was similar to that at 50 mg b.i.d. in Western patients [geometric mean (coefficient of variation) steady state area under the concentration‐time curve over the dosing interval (AUC(0–τ) ): 21.4 μM.h (52.3%) and 24.1 μM.h (53.6%), respectively]. Exposure–AE relationships could be described for neutropenia, stomatitis and diarrhoea, supporting the lower dosage of alisertib in Asia for global clinical development. Conclusions: Model‐based simulations support the achievement of similar alisertib exposures in patients in Asia who are administered a 40% lower dose compared with the Western population, thereby providing a quantitative clinical pharmacology bridging and regional dosing rationale for global drug development. Abstract : What is Already Known about this Subject: Alisertib is an Aurora kinase A inhibitor in development for haematological and nonhaematological malignancies. Ethnic differences may affect a medication's pharmacokinetics and benefit–risk profile, making quantitative clinical pharmacological characterization of these effects important, to optimize dosage in global drug development. The maximum tolerated dose of alisertib is 50 mg twice daily and 30 mg twice daily, respectively, in Western and East Asian patients. What this Study Adds: This study provided a global population pharmacokinetic model for alisertib that quantitatively describes the sources of interpatient variability in pharmacokinetics and estimates the effect of the East Asian region on the apparent oral clearance of this agent, to support appropriate dosing recommendations for global drug development.